Being you : a first conversation about gender - Madison, Megan; Ralli, Jessica (Madison, Megan. First conversations., 2022)
"While young children are avid observers and questioners of their world, adults often shut down or postpone conversations on complicated topics because it's hard to know where to begin. Research shows that talking about issues like race and gender from the age of two not only helps children understand what they see, but also increases self-awareness, self-esteem, and allows them to recognize and confront things that are unfair, like discrimination and prejudice. This second book in the series begins the conversation on gender, with a supportive approach that considers both the child and the adult. Stunning art accompanies the simple and interactive text, and the backmatter offers additional resources and ideas for extending this discussion"--Provided by publisher